2002
DOI: 10.1074/jbc.m109447200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mouse Cysteinyl Leukotriene Receptors mCysLT1 and mCysLT2

Abstract: Cysteinyl leukotrienes (LTs) are important proinflammatory mediators. Their precise roles in mice need to be elucidated to interpret mouse models of inflammatory diseases. For this purpose, we cloned and characterized mouse receptors for cysteinyl LTs, mCysLT 1 and mCysLT 2 . mCysLT 1 and mCysLT 2 were composed of 339 amino acids with 87.3% identity and 309 amino acids with 73.4% identity to human orthologues, respectively. A pharmacological difference was noted between mouse and human CysLT 2 . Pranlukast, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…ϩ RNA was hybridized with [ 32 P]dCTP-labeled probes of human p2y 9 /GPR23 and human ␤-actin, as described previously (16). The washed membrane was subjected to autoradiography for 4 days (p2y 9 /GPR23) or 3 h (␤-actin).…”
Section: Methodsmentioning
confidence: 99%
“…ϩ RNA was hybridized with [ 32 P]dCTP-labeled probes of human p2y 9 /GPR23 and human ␤-actin, as described previously (16). The washed membrane was subjected to autoradiography for 4 days (p2y 9 /GPR23) or 3 h (␤-actin).…”
Section: Methodsmentioning
confidence: 99%
“…RT-PCR for cysLT 1 receptor was conducted as previously described (31). The sense primer was 5Ј-CAA CGA ACT ATC CAC CTT CAC C-3Ј, and the antisense primer was 5Ј-AGC CTT CTC CTA AAG TTT CCA C-3Ј.…”
Section: Rt-pcrmentioning
confidence: 99%
“…We and others have reported that the mouse CysLT 1 receptor can function as a receptor for LTD 4 in transfected cells with a ligand preference similar to that of the human CysLT 1 receptor (19 -22). The mouse CysLT 2 receptor exhibits a ligand profile of LTC 4 Ն LTD 4 Ͼ Ͼ LTE 4 (22,23). In contrast to the extensive studies on the functions of the CysLT 1 receptor (24,25), the functional characterization of the CysLT 2 receptor has been limited because of a lack of specific competitive antagonists.…”
mentioning
confidence: 99%